Multivariate Granger causality between CO2 emissions, energy intensity and economic growth in Portugal: evidence from cointegration and causality analysis - Shahbaz, Muhammad; Jam, Farooq Ahmed; Bibi, Sadia; Loganathan, Nanthakumar (Technological and Economic Development of Economy, 2016)
The present study aims to investigate the relationship between economic growth, energy intensity and CO2 emissions by incorporating financial development in CO2 emissions function using Portuguese annual data over the period of 1971–2011. The unit root problem of variables is examined by applying Zivot-Andrews unit root test and the ARDL bounds testing approach is for long run relationship. The direction of causal relationship between the series is examined by the VECM Granger causality approach and robustness of causality analysis is tested by innovative accounting approach (IAA). Our empirical evidence confirmed that the variables are cointegrated for long run relationship. The results exposed that economic growth and energy intensity increase CO2 emissions, while financial development condenses it. The VECM Granger causality analysis showed the feedback effect between energy intensity and CO2 emissions, while economic growth and financial development Granger cause CO2 emissions. The study suggests that environment degradation can be controlled by using energy efficient technologies. Financial development can also play its role in improving the environmental quality by encouraging investment in energy efficient technology to enhance domestic production and save the environment from degradation. First published online: 09 Jul 2015